Priorities for Public Sector Research on Food Security and Nutrition - McDermott, John; Raney, Terri; Bouis, Howarth E. (2013)
Presentation by John McDermott, CGIAR; Terri Raney, FAO and Howarth Bouis, IFPRI. Food Security Futures I Conference on April 11, 2013 in Dublin, Ireland.